Safe limits of drinking: general practitioners' views. Issue 6485 (22nd June 1985) - Wallace, P; Cremona, A; Anderson, P
Abstract : A survey was carried out by questionnaire of general practitioners' views on what the safe upper limits of alcohol consumption are for health education for men and women. The results showed lower limits than those suggested by "alcohol experts" in a previous survey.